Analisis Mekanisme Seleksi Perangkat Desa di Desa Awa’ai Kecamatan Gunungsitoli Idanoi Kota Gunungsitoli - Gea, Arman Hikmat Damai; Hulu, Fatolosa; Telaumbanua, Eliagus; Mendrofa, Syah Abadi (Arden Jaya Publisher, 2024)
This research is titled “Analysis of the Village Apparatus Selection Mechanism in Awa'ai Village, Gunungsitoli Idanoi Sub-district, Gunungsitoli City” and aims to identify and evaluate the village apparatus selection process in the context of applicable regulations and the challenges faced in its implementation. The selection mechanism for village officials plays an important role in determining the quality of leadership and public services at the village level. Using a qualitative approach and case study method, the research collected data through in-depth interviews with village officials, community leaders, and residents, as well as analysis of relevant documents. The findings reveal that the selection mechanism for village officials in Awa'ai Village has followed the procedures stipulated by village regulations and relevant laws. However, a number of challenges also colored the selection process, such as changes in regulations that affected the stability of the mechanism, low community participation in decision-making, technological limitations in the implementation of the selection, as well as the impact of politicization and lack of training for village apparatus candidates. In an effort to overcome these obstacles, several recommendations were put forward to improve transparency, public participation, and integrity in the selection process in the future. The conclusion of this study confirms the need for continuous improvement in the selection system to produce competent village officials with integrity, in order to optimize services to the community.